Calcium and vitamin D supplementation in children with frequently relapsing and steroid-dependent nephrotic syndrome - Ayi Dilla Septarini; Taralan Tambunan; Pustika Amalia (Paediatrica Indonesiana, 2012)
Background Children with frequently relapsing and steroiddependentnephrotic syndrome (FRNS/SDNS) are at riskfor osteoporosis due to impaired metabolism of calcium andvitamin D.Objective To determine the effect of calcium and vitamin Dsupplementation on bone mineral density, serum ionized calciumlevels and serum 25-hydroxy-vitamin D levels in children withFRNS and SDNS.Methods A clinical trial with a before and after design wasperformed. Subjects were SDNS or FRNS pediatric patients 2: 5years of age. Subjects received 800 mg elemental calcium and 400IU vitamin D supplementation for 8 weeks. Serum ionized calcium,serum 25-hydroxy-vitamin D [25(0H)D], and bone mineral density(BMD) were determined before and after the supplementation.Results Of the 30 subjects, 28 completed the study. However,only 20 subjects underwent BMD determination before and aftersupplementation. Of the 28 subjects, 22 had hypocalcemia and 26had low vitamin D levels. Osteopenia was found in 14/20 subjects andosteoporosis was in 2/20 subjects. After 8 weeks of supplementation,mean serum ionized calcium increased from low [1.15 mmol/L (SDO.oJ)] to normal [1.18 mmol/L (SD 0.04)] (P< 0.001) levels, butmean serum 25(0H)D only increased from vitamin D deficiencycategory [20 ng/mL (SD 7 .7)] to vitamin D insufficiency category[25.5 ng/mL (7.7)] (P=0.010). Mean z-score BMD increased from-1.1 (SD 0.9) to -0.7 (SD 0.2) after supplementation (P<0.001).Conclusion Calcium vitamin D supplementation effectively increasedserum ionized calcium, serum 25 (OH)D, and BMD in subjectswith FRNS and SDNS. [Paediatr lndones. 2012;52:16-21].